Physics-informed deep learning characterizes morphodynamics of Asian soybean rust disease - Henry Cavanagh (Nature Portfolio, 2021)
Deep learning (DL) can be used to automatically extract complex features from dynamic systems. Here, the authors combine high-content imaging, DL and mechanistic models to extract and explain drug-induced morphological changes in the growth of the fungus responsible for Asian soybean rust.